OPTIMIZATION OF TITANIUM ALLOY GRINDING PROCESS BASED ON ELECTROMAGNETIC INDUCTION PREHEATING (Jixie qiangdu)
In order to optimize the titanium alloy workpiece surface finish and reduce the deterioration effect of surface residual stress caused by temperature gradient during grinding,a optimization of grinding process based on electromagnetic induction preheating was proposed.Firstly,the corresponding grinding process was modeled by 3D finite element method,and the grinding process under different grinding parameters and conditions were simulated and analyzed.Secondly,the results under different grinding parameters and conditions were analyzed to determine the influence mechanism of different parameters and conditions on grinding results.Finally,a set of simulation parameters were selected for corresponding experimental analysis and compared with the simulation results.The results show that the grinding process based on electromagnetic induction preheating can optimize the distribution of residual stress on the workpiece surface to a large extent,and the previous inference about the deterioration effect of temperature gradient in the grinding process can be verified by the corresponding results.